A direct four-electron process on Fe–N3 doped graphene for the oxygen reduction reaction: a theoretical perspective. Issue 38 (3rd May 2017) - Bai, Xiaowan; Zhao, Erjun; Wang, Wencheng; Wang, Ying; Li, Kai; Lin, Lin; Yang, Jucai; Sun, He; Wu, Zhijian
Abstract : The reaction mechanism for the ORR on Fe–N3 -Gra is investigated theoretically. Our results indicate that the ORR is a direct four-electron process, and the kinetically most favorable pathway is O2 hydrogenation. Abstract : As one of the potential candidates for electrocatalysis, non-precious transition metal and nitrogen co-doped graphene has attracted extensive attention in recent years. A deep understanding of the oxygen reduction reaction (ORR) mechanism including the specific active sites and reaction pathways will contribute to the further enhancement of the catalytic activity. In this study, the reaction mechanism for ORR on Fe–N3 doped graphene (Fe–N3 -Gra) is investigated theoretically. Our results show that Fe–N3 -Gra is thermodynamically stable. The ORR elementary reactions take place within a small region around the Fe–N3 moiety and its adjacent six C atoms. HOOH does not exist on the catalyst surface, indicating a direct four-electron process for Fe–N3 -Gra. The kinetically most favorable pathway is O2 hydrogenation, in which the formation of the second H2 O is the rate-determining step with an energy barrier of 0.87 eV. This value is close to 0.80 eV for pure Pt, suggesting that Fe–N3 -Gra could be a potential electrocatalyst. Free energy changes at different electrode potentials are also discussed.